Cricket as a Cultural Practice: An Ethnographic Study of the Pakistani Community in Tabuk - Al Moteb, Mohammed Ali Mohammed; Al-Mohsen, Mohsen Abdalrhman Mohsen (Journal of Humanities & Social Sciences, 2025)
The study aimed to identify the game of cricket among the Pakistani community in Tabuk, and to know their culture when playing cricket. The study community was the Pakistani community in Tabuk, and the study sample consisted of (28) individuals who were chosen in a purposive manner. The study used the ethnographic method and the observation and interview tools as criteria for content analysis. The study reached a number of results, the most important of which were: Cricket is very popular among the Pakistani community and other Asian communities in the Kingdom, and it promotes cultural values among members of the Pakistani community. In light of the study's findings, the study made several recommendations, including: paying attention to allocating cricket stadiums because it has become a global game, holding competitions between communities present in Tabuk, and forming cricket teams.
Keywords: cricket; community; Cultural practice